CONCEITOS EM CRISTALOGRAFIA ESTRUTUAL: UMA ABORDAGEM COMPREENSIVA DA LEI DE BRAGG E DO FATOR DE ESTRUTURA - Rafael P. Machado; Antônio C. Doriguetto (Química Nova)
It is not uncommon that as a chemistry course progresses, along with the deepening of the content studied, the tendency of not carefully revisiting the foundations of the concepts covered and deepened also increases. The understanding of the structure of matter that develops throughout the course, starting from the first concepts of atomic theory, going through chemical bonds, molecules, intermolecular interactions to the study of how matter is aggregated in the solid state, is an example of knowledge that grows in depth and complexity. In this context, crystallography presents itself as a vast interdisciplinary area that contributes to understanding the matter. This article explores fundamental mathematical, historical, chemical, and physical concepts, connecting them to offer a more comprehensive and logically coherent understanding of key crystallography principles.